MOLNÁR JÁNOS, “Virágok a templomban”. Zsoboki (kalotaszegi) kötények díszítőmotívumai “[The Flowers of the Church]”. The Ornamentical Motifs of the Aprons from Zsobok (Kalotaszeg), Ed. Egyetemi Műhely, Bolyai Társaság – Kolozsvár, 2009. - COCA, Gabriela (Studia Universitatis Babes-Bolyai Musica, 2009)
[1]The book of the University Professor Molnár János PhD was released recently with the help of the Bolyai Society of Cluj-Napoca. Regarding the contents of this Ethnographic folkloric monograph, we quote the summary of the book as follows: “The traditional costumes from Kalotaszeg have been transformed during the years in ceremonial dresses worn in church festivals, Sunday’s services. The church is the place where the traditional costumes appear in an absolute beauty and harmony even if it is only a Sunday morning ceremony, not necessary a well-known high day. When the members of the community are dressed in these traditional clothes, the church not only becomes a colourful place but it burst out into bloom. This blooming inspired the title of the book: The flowers of the church, having its main aim to present the most beautiful and the most decorative piece of women traditional clothing: the apron, and its ornamental motifs, flower - patterned composition, the structure and symbol of the design, and the correlation among the elements, motifs. The book contains more chapters. In the first part the author presents the geographical location, the history of the village, how the village came into being, the origin of its name, first of all the history of the church and the historical legends linking to this settlement. This is followed by a socio-graphical presentation, which explains the demographical changes of the village. The chapter ends with the history of the Reformed School. The description of the traditional costume is in the next part of the book: the presentation of the apron containing very detailed description of the pattern, how it is sewed, who are sewing today and the pattern-motifs are for which occasion and age. The description is followed by the presentation of each pattern, as well as the decorative motifs – for example: wasp, rose, tulip, daisy, carnation, lily of valley, ear, different fruits, bird, stars, wind and fire. Coming to an end of the volume, we find the references. In the third and the last part of the volume, we find a very colourful presentation and description of the 120 apron models, 47 simple aprons (without ribbons) and 73 aprons with ribbon, totally 120 and 250 photos. In the attachment we find another 50 photos with the traditional costumes.”[2] [1] Zsobok (Romanian: Jebuc) is a village from the region Kalotaszeg (Ţara Călatei), from Romania. [2] Molnár, János, quoted op., p. 193.